Advances in imaging and electron physics. (Advances in imaging and electron physics, 2010)
Advances in Imaging and Electron Physics merges two long-running serials--Advances in Electronics and Electron Physics and Advances in Optical and Electron Microscopy. This series features extended articles on the physics of electron devices (especially semiconductor devices), particle optics at high and low energies, microlithography, image science and digital image processing, electromagnetic wave propagation, electron microscopy, and the computing methods used in all these domains. * Contributions from leading international scholars and industry experts * Discusses hot topic areas and presents current and future research trends * Invaluable reference and guide for physicists, engineers and mathematicians.